Pemberdayaan UMKM Desa Plawangan Rembang dalam Pengembangan Produksi dan Pemasaran Melalui Pendampingan Kreatif dan Digital - Pramujati, Windya Harieska; Tahwin, Muhammad; Melfasari, Anisha; Maskuri, Maskuri; Amanti, Dyah Lutfi; Anggoro, Zidan Dwi (STIE Pelita Nusantara, 2024)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in supporting Indonesia's economy. However, MSMEs often face various challenges that hinder their growth, including limitations in production development, lack of effective promotional strategies, and absence of business legality. In the digital era, there are numerous new opportunities that can be leveraged for MSME development. To address these challenges, concrete steps and appropriate assistance are required. This study discusses the assistance provided to Donutte_Al, an MSME engaged in donut production and sales in Plawangan Village, Kragan Sub-district, Rembang Regency, through the Business Work Study Program (KKU) of YPPI Rembang University. The aim of this assistance is to optimize potential and overcome challenges through creative and digital support, including the creation of MSME banners and brochures, preparation of risk-based business licensing documents to obtain a Business Identification Number (NIB), as well as marketing assistance and training using the canva application. The objective of this collaboration is to provide strategic and effective steps for MSME development, create positive synergy, and contribute to local economic growth and community welfare improvement.